One Health Surveillance: A Matrix to Evaluate Multisectoral Collaboration - Bordier, Marion; Delavenne, Camille; Nguyen, Dung Thuy Thi; Goutard, Flavie Luce; Hendrikx, Pascal (Frontiers in Veterinary Science, 2019)
The international community and governmental organisations are actively calling for the implementation of One Health (OH) surveillance systems to target health hazards involving humans, animals and their environment. In our view, the main characteristic of a OH surveillance system is the collaboration of institutions and disciplines operating within the different sectors to plan, coordinate and implement the surveillance process. However, the multi-sectoral organisational models and possible collaborative modalities implemented throughout the surveillance process are multi-fold, and depend on the objective and context of the surveillance. The purpose of this study is to define a matrix to evaluate the quality and appropriateness of multi-sectoral collaboration through an in-depth analysis of its organisation, operation and functions. We developed a first list of evaluation attributes based on the (i) characteristics of the organisation, operation and functionality of multi-sectoral surveillance systems and (ii) existing attributes for the evaluation of health surveillance systems and OH initiatives. These attributes were submitted to a two-round expert opinion elicitation for review and validation. The final list of attributes included 23 organisational attributes and 9 functional attributes, to which were added 3 organisational indexes measuring the overall organisation of collaboration. 75 criteria were then defined to evaluate the level of satisfaction for the attributes. The criteria were scored following a 4-tiered scoring grid. Graphical representations allowed for an easy overview of the evaluation results for both attributes and indexes. This evaluation matrix is the first to allow an in-depth analysis of collaboration in a multi-sectoral surveillance system and is the preliminary step towards the creation of a fully stand-alone tool for the evaluation of collaboration. After field-testing its practical application and adaptability to different contexts, this tool could be very useful in identifying the strengths and weaknesses of collaboration occurring in a multi-sectoral surveillance system.